The Relationship Between Housing Sanitation Factors and the Incidence of Acute Respiratory Infections (ARI) in the Batulappa Health Center Work Area - Sudirman, Sudirman; Marwah, Marwah; Taslim, Taslim; Armadi, Armadi; Rudini, Muh.; Sudirman (Journal of Community Health Provision, 2024)
Home and environmental sanitation are closely related to the incidence of infectious diseases, especially ARI (Taylor, 2002). Several things that can affect the incidence of ARI in toddlers are the physical condition of the house, cleanliness of the house, density of residents and air pollution in the house (Iswarini and Wahyu, 2006). This type of research is analytical survey research with a cross-sectional study approach. This research was conducted in the Batulappa Health Center Working Area, Batulappa District, Pinrang Regency for 1 (one) month, namely from October 11 to October 31, 2022 with a sample size of 95 respondents. The results of the study showed that there was a relationship between occupant density, building type, and house ventilation with the incidence of ARI in the working area of the Batulappa Health Center, Batulappa District, Pinrang Regency. Suggestions in this study It is hoped that all people, especially those in the Batulappa Health Center work area, will maintain personal and environmental hygiene and prevent children from coming into contact with ARI sufferers.